PENGARUH MOTIVASI DAN KEPRIBADIAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA ( Studi pada Badan Pelaksana Penyuluhan Kabupaten Temanggung) - 11.52.02.0109, Budi Susilo (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to examine whether motivation and personality positively and significantly affecting performance through job satisfaction in BadanPelaksanaPenyuluhan, District of Temanggung. This study conducted on employees in BadanPelaksanaPenyuluhan, District of Temanggung that has civil servant status. The method used in this study was census, while the statistical technique used is validity test with matrix component, reliability test with cronbach alpha, multiple regression analysis, t-test and adjusted-R square. The results show that motivation positively and significantly influencing job satisfaction, personality positively and significantly influencing job satisfaction, motivation positively and significantly influencing performance, personality positively and significantly influencing performance, job satisfaction positively and significantly influencing performance, job satisfaction mediating the influence of motivation on performance, whereas job satisfaction was not mediating personality influence on performance. Keywords: Motivation, Personality, Job Satisfaction, Performance